The Effects of The Covid-19 Pandemic on The Spanish Labour Market - Dagmara BAGROWSKA; Szymon MACHAŁA; Norbert CHAMIER-GLISZCZYNSKI (Communications of International Proceedings, 2021)
This paper presents Spain's economic problems before and during the outbreak of the global COVID-19 pandemic. The aim of the study was to link the current epidemiological situation with the critical economic situation in the Spanish economy, particularly in the market for tourist goods and services, the labor market and to conduct an electronic survey among the population, allowing the study of public sentiment and any differences in the views of the Spanish population on the labor market in the era of the COVID-19 pandemic.
Keywords: Spain; COVID-19; economy; labour market